If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + 2 = 5y + 7 Reorder the terms: 2 + 6y = 5y + 7 Reorder the terms: 2 + 6y = 7 + 5y Solving 2 + 6y = 7 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 2 + 6y + -5y = 7 + 5y + -5y Combine like terms: 6y + -5y = 1y 2 + 1y = 7 + 5y + -5y Combine like terms: 5y + -5y = 0 2 + 1y = 7 + 0 2 + 1y = 7 Add '-2' to each side of the equation. 2 + -2 + 1y = 7 + -2 Combine like terms: 2 + -2 = 0 0 + 1y = 7 + -2 1y = 7 + -2 Combine like terms: 7 + -2 = 5 1y = 5 Divide each side by '1'. y = 5 Simplifying y = 5
| y=-2/3•-6-1 | | -1/4d-1/4=2 | | f-4.4=7.2 | | -8-2=16-3x | | 5/2-1/3 | | 1/2(x-4)-2.2(x-1.4)=2(1.35)-4x | | y+3y-27=41 | | b+0.4=0.7 | | 15=i-4 | | (1/4a)÷3.6=-a-0.5 | | 20=c+14 | | 1/4×a | | 17=d-19 | | V-14=20 | | 1/4×a/3.6 | | 14x^2-3x+15x^3= | | 1/4a/3.6=-a-0.5 | | 6/7*7/6 | | 24x+32x^2-26x= | | 12=d-4 | | (-2.2x+5)(-2)= | | -4(x+6)+5x= | | H-59=72 | | E-21=37 | | 3y-15z+12x= | | T-14=7 | | k+m/-7=nfork | | Z+5=7 | | 2a+3=3a+2 | | 2/3x−5=1/2x−3. | | 8-7(-5+x)-2x= | | 1/2m+2/3≤2/3m+2. |